Pengaruh Working Capital Turnover, Total Asset Turnover, dan Capital Intensity Terhadap Profit Growth Pada Sub Sektor Makanan & Minuman Yang Terdaftar di BEI Tahun (2020-2024) - Elisabet Giawa; Asnahwati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the effect of Working Capital Turnover (WCT), Total Asset Turnover (TATO), and Capital Intensity (CI) on profit growth in the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. Profit growth is a crucial indicator of a company’s financial performance and is influenced by various operational and resource efficiency factors. The research employs a quantitative method using multiple linear regression analysis. The data used are secondary data obtained from the annual financial reports of food and beverage sub-sector companies listed on the IDX. Hypotheses were tested both partially (t-test) and simultaneously (F-test) with a significance level of 5%. The results show that Working Capital Turnover (WCT) has a positive and significant partial effect on profit growth. Total Asset Turnover (TATO), however, does not have a positive and significant effect. In contrast, Capital Intensity (CI) has a negative and significant partial effect on profit growth. Simultaneously, all three independent variables have a positive and significant influence on the profit growth of the companies. These findings highlight the importance of efficient working capital management in enhancing profitability, as well as the need to evaluate asset structure and capital investment policies to avoid a decline in financial performance. Therefore, companies are advised to develop integrated financial strategies to support sustainable profit growth.